Occurrence of plastics ingested by Atlantic cod (Gadus morhua) destined for human consumption (Fogo Island, Newfoundland and Labrador). (April 2020) - Saturno, Jacquelyn; Liboiron, Max; Ammendolia, Justine; Healey, Natasha; Earles, Elise; Duman, Nadia; Schoot, Ignace; Morris, Tristen; Favaro, Brett
Abstract: In the province of Newfoundland and Labrador, fishing is a core occupation and also a source of marine plastic pollution. To look at this relationship, we examined 216 gastrointestinal tracts of Atlantic cod ( Gadus morhua ) caught by commercial fishers at Fogo Island, Newfoundland and Labrador, Canada. We found three tracts contained plastic for a frequency of occurrence of 1.4%. While this result is consistent with other cod sampled in the province, this study found two gastrointestinal tracts contained intact bait bags, used in commercial pots, and the third tract contained a polypropylene thread, likely originating from fishing rope. Our findings demonstrate the frequency of plastic ingestion in this region is low, but fishing-gear related plastics represent a key source of marine plastics in the region that should be addressed. Highlights: Frequency of occurrence (%FO) of plastic ingestion is 1.4% for Atlantic cod ( n  = 216) %FO results are consistent with previous studies on Atlantic cod in Newfoundland and Labrador Sources of 2/3 ingested plastics were confirmed fishing gear-related Two polyethylene bait bags and one polypropylene thread were found in GI tracts.